The great depression ahead : how to prosper in the crash following the greatest boom in history - Dent, Harry S., Jr., 1950- (Free Press, 2009)
Renowned economic forecaster Harry S. Dent, Jr., explains that by 2010 rising oil prices and peaking generational spending will lead to a more severe downtrend for the global economy and individual investors alike. He outlines the critical issues that will face us and offers long- and short-term tactics for weathering the storm.